2014
DOI: 10.4103/2230-8210.140242
|View full text |Cite
|
Sign up to set email alerts
|

Management of Type 2 diabetes in Ramadan: Low-ratio premix insulin working group practical advice

Abstract: The challenge of insulin use during Ramadan could be minimized, if people with diabetes are metabolically stable and are provided with structured education for at least 2–3 months pre-Ramadan. Although, American diabetes association (ADA) recommendations 2010 and South Asian Consensus Guideline 2012 deal with management of diabetes in Ramadan and changes in insulin dosage, no specific guidance on widely prescribed low-ratio premix insulin is currently available. Hence, the working group for insulin therapy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…2). Most importantly, glucose levels should be checked at any time when symptoms of hypoglycaemia are recognised [23]. All patients should comprehend the dangers of low and high blood glucose levels, know when to break the fast, and must not fast if they are unwell [8].…”
Section: Adults With T1dmmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Most importantly, glucose levels should be checked at any time when symptoms of hypoglycaemia are recognised [23]. All patients should comprehend the dangers of low and high blood glucose levels, know when to break the fast, and must not fast if they are unwell [8].…”
Section: Adults With T1dmmentioning
confidence: 99%
“…2). Patients should break the fast if blood glucose is <70 mg/dL (3.9 mmol/L) or >300 mg/dL (16.7 mmol/L) and should not fast if they feel unwell [23]. Low risk patients also need to perform SMBG at the following times: pre-suhoor, midday, pre-iftar and whenever symptoms of hypoglycaemia or acute illness occur [23].…”
mentioning
confidence: 99%
“…Table 2 lists recommendations for insulin self-titration during the Ramadan period. The ‘Low-Ratio Premix Insulin Working Group’ recently reported a practical outline on how to adjust insulin during the fasting period, based on premeal blood glucose levels and the history of hypoglycemia 23. This group also recommended a trial fast for three consecutive days before Ramadan to help in detecting hypoglycemia risk and for guiding the self-titration of premix insulin dosage.…”
Section: Use Of Glucose-lowering Medications During Ramadanmentioning
confidence: 99%
“…The EPIDIAR study reported that approximately 50% of participants with diabetes experienced a change in lifestyle, with the proportion of participants with T2DM experiencing a change ranging from 25.2% to 54.4% for oral antidiabetic drug (OAD), insulin dose, weight, physical activity, sugar intake, food intake, fluid intake, and sleep duration [4]. Ramadan-focused education can enable individuals to adjust their lifestyle during Ramadan, minimize the risk of hypoglycemic events and weight gain, and be tempered to the local practices and seasonal time of year when Ramadan occurs [7,10,[12][13][14][15][16]. A recent prospective study found that pre-Ramadan education reduced acute complications, including hypoglycemia risk and low-density lipoprotein (LDL) cholesterol and improved high-density lipoprotein (HDL) cholesterol [17].…”
Section: Introductionmentioning
confidence: 99%